Nanoparticles within WWTP sludges have minimal impact on leachate quality and soil microbial community structure and function. (April 2016) - Durenkamp, Mark; Pawlett, Mark; Ritz, Karl; Harris, Jim A.; Neal, Andrew L.; McGrath, Steve P.
Abstract: One of the main pathways by which engineered nanoparticles (ENPs) enter the environment is through land application of waste water treatment plant (WWTP) sewage sludges. WWTP sludges, enriched with Ag and ZnO ENPs or their corresponding soluble metal salts during anaerobic digestion and subsequently mixed with soil (targeting a final concentration of 1400 and 140 mg/kg for Zn and Ag, respectively), were subjected to 6 months of ageing and leaching in lysimeter columns outdoors. Amounts of Zn and Ag leached were very low, accounting for <0.3% and <1.4% of the total Zn and Ag, respectively. No differences in total leaching rates were observed between treatments of Zn or Ag originally input to WWTP as ENP or salt forms. Phospholipid fatty acid profiling indicated a reduction in the fungal component of the soil microbial community upon metal exposure. However, overall, the leachate composition and response of the soil microbial community following addition of sewage sludge enriched either with ENPs or metal salts was very similar. Highlights: Adding nanoparticles (NPs) to influent of a WWTP provides a realistic exposure route. ZnO and Ag NP and metal salt soil/sludges were aged 6 months in outdoor columns. Amounts of Zn and Ag leached were very low in NP and metal salt treatments. Both types of metal exposure reduced the fungal component of the soil microbial community. Responses in NP and metal salt soil/sludges were very similar overall. Abstract : The fate and effects of ENPs are studied under realistic conditions: ENPs were added to the influent of a Waste Water Treatment Plant and the resulting sewage sludges mixed with soil in lysimeters.